La atención y servicio al cliente como estrategia de marketing para el fortalecimiento institucional de la Cooperativa de Ahorro y Crédito Juan Pio de Mora. Cía. Ltda. (matriz) en el cantón San Miguel, año 2018. - Morejón Camacho, Jhair Esteeven (2018)
The Juan Pio de Mora Savings and Credit Cooperative. Inc. Ltda. (Matrix). It is located in the canton San Miguel de Bolívar currently has 6877 members who enjoy the benefits offered by the institution such as their products and services. The purpose of this research project is to improve its long-term customer service and attention in order to strengthen the institution and be better than the competition every day increasing partners to improve profitability, profits and be solvent in the market. Through this project, employees can be trained to provide a quality service that customers are satisfied with, visit the place and acquire their products and services. The clients will be able to present their complaints in a suggestion box, which the financial institution will be able to notice its shortcomings in order to improve them. This is very helpful because they are referencing what the client is needing and demanding when purchasing their products or services. With the guarantees provided by the entity, they feel safe and motivated when investing their money, managing themselves with a guide protocol so that they can obtain information from clients in order to satisfy their needs and be able to retain them.